E-portfolio by means of Google Apps in the monitoring of linhvomethodological competence of students' philologists - O. Ye. Ishutina (Academy of Cognitive and Natural Sciences, 2014)
Research goals: consideration the method of e-portfolio created by the Google Apps for Education in the system of monitoring methods of students' linhvomethodological competence. Research objectives: to distinguish of portfolio method as one that allows you to monitor and objectively evaluate the process and result of the formation of both theoretical and practical components linhvomethodological competence of the student. Object of research: monitoring of linhvomethodological competence of students' philologists. Subject of research: e-portfolio by means of Google Apps in the monitoring of linhvomethodological competence of students' philologists. Research methods used: analysis of state standards and publications. Results of the research. Experimental study shows that the students' forming of electronic methodological portfolio by means of Google cloud services allows the teacher to monitor developments in linhvomethodological competence of prospective native language teachers, which is an integral part of quality education monitoring. The main conclusions and recommendations: organization of work on e-portfolio method by use of Google cloud services in the professional training of students can objectively assess the dynamics of linhvomethodological competence of future teachers of their native language, which is an integral part of monitoring of quality of education.